OBSERVANCE OF SAFETY RULES WHEN PERFORMING EDUCATIONAL LABORATORY WORKS - M. S. Nabiyeva; R. A. Hakimova; Sh. Sh. Ramazonova; J. O. Arabov (Modern American Journals, 2025)
This article will highlight the importance of observance of safety rules when performing educational laboratory work. The need to observe safety rules in order to minimize the risks that arise in the process of laboratory research and experiments is emphasized. The article presents the potential hazards of working in chemistry, physics, biological and electronics laboratories, as well as practical recommendations for their prevention and safety.
Keywords: educational laboratory work, equipment safety, safety rules, chemistry laboratory, physics laboratory, biological laboratory, electronics laboratory, hazards, protective equipment, laboratory security.